What are you afraid of: Collective leadership and its learning implica tions - Raelin, Joseph A (Management Learning)
In this provocation, the author attempts to cite the advantages of col lective leadership while acknowledging the objections and fears of cha llengers. Collective leadership is seen as remote because it defies th e traditional view of leadership as an individualistic attractive qual ity that not only protects us but is efficient when applied. Neverthel ess, the collective alternative may not only be advisable but required in a connected world featuring a networked economy. The contemporary socio-politico-economic environment requires the contribution of, crea tivity from, and collaboration among multiple agents providing a dynam ic concentration of management and knowledge. If we are to accept and recognize the contribution of a collective leadership, its development would require an entirely different learning model. In particular, co llective leadership development occurs as an acute immersion into the practices that are embedded within in situ material–discursive relatio ns—in other words, among people, objects, and their institutions.